Mutu Modal Manusia dan Pertumbuhan Ekonomi - H Hardjanto (Institut Pertanian Bogor (IPB University), 2002)
This paper present a correlation between human capital and economic grawrh. There are two important points concerning this correlation, First, human capital should be put on the same priorih as other factor in economic growth. Second, human capital has a significant impact on the economic growth.